2018
DOI: 10.1021/acs.jafc.8b05723
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling of the Fishy Off-Flavor in Steam-Treated Rapeseed Oil Using the Sensomics Concept

Abstract: The sensomics concept was applied to two steam-treated rapeseed oils, one eliciting a fishy off-flavor (OF) and the other the desired aroma attributes (PC = positive control). After screening the most important odorants via comparative aroma extract dilution analysis, identification experiments and quantitation via stable isotope dilution analysis (SIDA) using gas chromatography−mass spectrometry (GC-MS) were performed. Only five compounds differed in their concentrations by a factor ≥5. In addition, trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…This was particularly noticed for rapeseed/canola oil in which ammonia was generated from the breakdown of glucosinolates and/or sinapine. This was nicely demonstrated by Matheis and Granvogl (2019a) in their recent research findings. In addition, the authors (Matheis and Granvogl, 2016) also found that the main difference of key odorant between desired sensory attributes and fusty/musty off-flavor in rapeseed oils was the discrepancy of concentration of certain compounds, such as 2-and 3-methylbutanoic acid, 2-methoxyphenol, and ethyl 2-methylbutanoate.…”
Section: Fishy Fusty/musty Off-flavor In Non-fish Oilsmentioning
confidence: 52%
“…This was particularly noticed for rapeseed/canola oil in which ammonia was generated from the breakdown of glucosinolates and/or sinapine. This was nicely demonstrated by Matheis and Granvogl (2019a) in their recent research findings. In addition, the authors (Matheis and Granvogl, 2016) also found that the main difference of key odorant between desired sensory attributes and fusty/musty off-flavor in rapeseed oils was the discrepancy of concentration of certain compounds, such as 2-and 3-methylbutanoic acid, 2-methoxyphenol, and ethyl 2-methylbutanoate.…”
Section: Fishy Fusty/musty Off-flavor In Non-fish Oilsmentioning
confidence: 52%
“…It was shown that phosphatidylcholine can generate trimethylamine in soybean oil (Jiang et al., 2016). Thus, Matheis and Granvogl (2019a) supposed that trimethylamine was formed during the steaming process from sinapine (bearing a choline ester in the side chain analog to phosphatidylcholine) as a possible precursor. Overall, the fishy smell might be caused by the synergism of several volatile compounds, which needs further research.…”
Section: Flavor Compounds In Rapeseed Oilmentioning
confidence: 99%
“…Further, some odorants might also be overlapped by the solvent peak during GC analysis (Parker, 2015). Thus, the HS technique is often applied in parallel to SAFE to identify very volatile aroma‐active compounds co‐eluting with the solvent peak, for example, dimethyl sulfide and methanethiol (Matheis & Granvogl, 2019a; Ortner et al., 2016). This combination ends up with a suitable analytical approach to detect all aroma‐active compounds in food.…”
Section: Flavor Analysis Techniques Of Rapeseed Oilmentioning
confidence: 99%
See 2 more Smart Citations